Determinantes das ofertas de açúcar e de álcool paranaenses (1981 a 2006): uma análise de co-integração - Dias, Luiz Carlos (2008)
The beginning of 90s is marked by a new dynamic of Brazilian sugar cane agribusiness. The disconnection of the State apparatus, which was responsible for the activities management at that time, forced the sector to an adjustment in a free market context that, since then, has been experiencing significant advances, both in internal and external markets. The investigation model proposed was implemented using the augmented Dickey-Fuller (ADF) unit root test and the cointegration test by Johansen in this research for sugar and alcohol paranaense s. For the sugar, the results pointed that: 1% rise in the agricultural income variable, will increase 1.24% in the sugar supply, 1% rise in the average price of sugar cane causes a fall of 1.18% in the sugar supply, a variation of 1% in the national average sugar price causes an increase of 0.73% in its supply; by raising 1% in the average price variable of international sugar (within two years of delay) there is a growth in the sugar supply of 0.37%. In relation to the alcohol supply, an increase in its average price (within a year of delay) raises the supply of the same product in 0.77%; if the average price of the international sugar rises (within a year of delay) in 1%, it generates a drop in the alcohol supply of 0.42%. With these results, it can be affirmed that although both products are from the same industry, sugar causes an interference in the provision of alcohol greater than the opposite, confirming that, despite the new dynamic given to the alcohol, this product can still be considered a residual one in respect to the sugar production in Paraná State. Despite the technological level achieved by this State in the sector, the agricultural income still determines the biggest rise in the sugar supply and it is one of the main variables for the alcohol supply expansion in Paraná State.